Intermittent time-set technique controlling the temperature of magnetic-hyperthermia-ablation for tumor therapy. Issue 30 (3rd May 2018) - Tang, Xiuzhen; Xu, Yanjun; Chen, Jie; Ying, Tao; Wang, Longchen; Jiang, Lixin; Wang, Yan; Wang, Zhenhai; Ling, Yi; Wang, Fengjuan; Yao, Li; Ran, Haitao; et al.
Abstract : Magnetic-hyperthermia-ablation is considered as an effective and minimally invasive technology for tumor therapy. Abstract : Magnetic-hyperthermia-ablation is considered as an effective and minimally invasive technology for tumor therapy. However, inappropriate temperature control could induce an excessively high temperature which brings potential safety problems and limits clinical transformation of this technique. Herein, aiming to control the temperature during magnetic hyperthermia ablation, we develop an intermittent time-set technique for temperature control in magnetic hyperthermia ablation of tumors using a polylactic- co -glycolic acid (PLGA)-Fe3 O4 implant. In vitro, the intermittent time is set as follows: tubes are continuously heated for 110 seconds. Then the heating process is paused for 20 seconds, and then the tubes are reheated for 10 seconds, followed by repeating the last two processes. The temperature elevation profile upon magnetic hyperthermia interestingly also demonstrates good controllability despite some differences in time-setting between in vitro and in vivo . The in vivo results show the temperature fluctuates within the range of 6.45 ± 1.34 °C after reaching the target temperature. Furthermore, we observe the deformation of an implant employing three-dimensional (3D) ultrasound to better understand the temperature change. The results show no significant deformation of the implant after being heated. The microscopic images prove that this simple technique can successfully cause tumor regression. This temperature control technique provides great benefits for hyperthermia ablation against tumors, advancing the magnetic hyperthermal ablation technology in clinical translation.